Intracellular Calcium Deficits in Drosophila Cholinergic Neurons Expressing Wild Type or FAD-Mutant Presenilin - Michno, Kinga (Public Library of Science, 2009)

(untitled)
Much of our current understanding about neurodegenerative diseases can be attributed to the study of inherited forms of these disorders. For example, mutations in the presenilin 1 and 2 genes have been linked to early onset familial forms of Alzheimer's disease (FAD). Using the Drosophila central nervous system as a model we have investigated the role of presenilin in one of the earliest cellular defects associated with Alzheimer's disease, intracellular calcium deregulation. We show that expression of either wild type or FAD-mutant presenilin in Drosophila CNS neurons has no impact on resting calcium levels but does give rise to deficits in intracellular calcium stores. Furthermore, we show that a loss-of-function mutation in calmodulin, a key regulator of intracellular calcium, can suppress presenilin-induced deficits in calcium stores. Our data support a model whereby presenilin plays a role in regulating intracellular calcium stores and demonstrate that Drosophila can be used to study the link between presenilin and calcium deregulation.